Studying the brightest radio sources in the southern sky - Sejake, Precious Katlego (Rhodes University, Faculty of Science, Department of Physics and Electronics)
Active Galactic Nuclei (AGN) are among the most remarkable and powerful extragalactic radio sources in the Universe. The study of AGN enables us to understand better the critical mechanisms leading to the launch of radio jets, and its link to the central engine. Radio jets are thought to impact their host galaxy by promoting or suppressing star formation. By studying AGN, we can better understand their formation, evolution, and environment. The host galaxy cross-identification is a crucial step to be carried out to build a multi-wavelength analysis of powerful radio sources; AGN. The GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) 4Jy (G4Jy) Sample comprises 1,863 of the powerful radio sources in the southern sky. However, 140 sources from the G4Jy Sample were followed-up with the Open Time on MeerKAT. Of these 140 sources, 126 had an ambiguous host galaxy, and 13 had an identified host galaxy; however, there were some discrepancies in the literature concerning the host galaxy. The host-galaxy identification of these sources is limited by the poor resolution of radio data at 25" to 45". This study aims to assess the radio morphology of these 140 sources and identify their host galaxy using the â‡  7" resolution images from MeerKAT in conjunction with datasets at other wavelengths. This analysis is carried out by visually inspecting the overlays. The overlays comprise radio contours from 150 MHz, 200 MHz, 843/1400 MHz and 1300 MHz overlaid on the mid-infrared image (3.4 Î¼m). The MeerKAT images reveal sources with various radio morphologies. While most of the sources have radio morphology of typical symmetric lobes, 10 radio sources have head-tail morphology, 14 are wide-angle tail (WAT), and 5 have X-, S- /Z-shaped morphology. Overall, we find host galaxies for 70% of the sources in the sample, with the remainder comprising sources with ambiguous host galaxy (20.7%) and sources with a faint mid-infrared host galaxy (9.3%). These results highlight the importance of angular resolution and sensitivity for morphological classification and host galaxy cross-identification.
Keywords: Galaxies -- Formation; Galaxies -- Evolution; Active galaxies; Radio galaxies; Radio sources (Astronomy); Southern sky (Astronomy)